2018
DOI: 10.5897/ajb2018.16406
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among elite chickpea (Cicer arietinum L.) varieties of Ethiopia based on inter simple sequence repeat markers

Abstract: The inter simple sequence repeat (ISSR) marker was used in this study for genetic fingerprinting and identification of released chickpea varieties and for the determination of the genetic relationships among these cultivars. A total of 19 released chickpea varieties were subjected to ISSR analysis with the objective of evaluating the genetic diversity among the cultivars. A total of 20 ISSR primers were initially screened and later based on their reproducibility and polymorphism, four of them were selected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The report is supported by other authors who reported the presence of genotypic variability in chickpea; such as Kumar et al (1999), Nimbalkar (2000), Wahid and Ahmad (1999) who observed significant variation for a number of seeds per pod and per plant, seeds per plant, hundred seed weight and yield per plant, respectively. Several chickpea investigations recorded significant genotypic differences among the crop collections studied by them (Chander et al, 2001;Abdalla et al, 2003;Zerihun et al, 2018).…”
Section: Analysis Of Variancementioning
confidence: 99%
“…The report is supported by other authors who reported the presence of genotypic variability in chickpea; such as Kumar et al (1999), Nimbalkar (2000), Wahid and Ahmad (1999) who observed significant variation for a number of seeds per pod and per plant, seeds per plant, hundred seed weight and yield per plant, respectively. Several chickpea investigations recorded significant genotypic differences among the crop collections studied by them (Chander et al, 2001;Abdalla et al, 2003;Zerihun et al, 2018).…”
Section: Analysis Of Variancementioning
confidence: 99%
“…There are several reports about genetic diversity, germplasm or seed of plant (Admas and Tesfaye, 2017;Ali et al, 2018;Arantes et al, 2018;Chalachew et al, 2017;Chandra et al, 2017;Daniel et al, 2017;Dilooshi et al, 2016;Santos et al, 2017;Ejigu et al, 2018;Emmanuel et al, 2018;Isaac et al, 2016;Lopez-Puc and Rodriguez-Buenfil, 2017;Revolti et al, 2018;Miccah et al, 2016;Mohammad et al, 2016;Mounawer et al, 2016;Mulima et al, 2018;Ochieng et al, 2015;Pacôme et al, 2016;Raimundo et al, 2015;Rodrigues et al, 2016;Tadesse et al, 2018;Titilayo et al, 2018;Zerihun et al, 2018), fungi (Edelvio, 2018;Ling et al, 2016;Shubha and Srinivas, 2017), bacteria (Chaohe et al, 2015;Paul et al, 2016), and virus (Chikoti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%